2014
DOI: 10.1016/j.nbd.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of Alzheimer's disease using PiB and FDG PET

Abstract: Use of biomarkers in the detection of early and preclinical Alzheimer’s disease (AD) has become of central importance following publication of the NIA-Alzheimer’s Association revised criteria for the diagnosis of AD, mild cognitive impairment (MCI) and preclinical AD. The use of in vivo amyloid imaging agents, such a Pittsburgh Compound-B and markers of neurodegeneration, such as fluoro-2-deoxy-D-glucose (FDG) are able to detect early AD pathological processes and subsequent neurodegeneration. Imaging with PiB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(127 citation statements)
references
References 94 publications
5
119
0
3
Order By: Relevance
“…13,147 Amyloid and tau imaging with positron emission tomography could also be helpful to diagnose comorbidity with AD in the patients with mixed disease, 145 with the caveat that amyloid deposits can also be present in cognitively normal individuals. 146 Biochemical CSF studies provide the third axis of diagnosis; elevated albumin ratio indicates that the BBB is compromised, which is more likely to occur in SVD than in AD. Furthermore, CSF shows changes in proteins associated with AD, including A 42 and pTau.…”
Section: An Approach To Targeted Treatment Trialsmentioning
confidence: 99%
“…13,147 Amyloid and tau imaging with positron emission tomography could also be helpful to diagnose comorbidity with AD in the patients with mixed disease, 145 with the caveat that amyloid deposits can also be present in cognitively normal individuals. 146 Biochemical CSF studies provide the third axis of diagnosis; elevated albumin ratio indicates that the BBB is compromised, which is more likely to occur in SVD than in AD. Furthermore, CSF shows changes in proteins associated with AD, including A 42 and pTau.…”
Section: An Approach To Targeted Treatment Trialsmentioning
confidence: 99%
“…According to Sixsmith and Gutman [1] games are a part of technology that developed for elderly people to allow them to experience enjoyable moments in their life. In addition, Cohen and Klunk [39] said leisure technology such as playing games is a relaxing method for elderly people to improve their cognitive thinking and memory to prevent Mild Cognitive Impairment (MCI), which leads to Alzheimer's disease at a later stage. The outcome of this study also showed that elderly people enjoyed the games with less difficulty such as eye fatigue and body aches.…”
Section: ) Sectionmentioning
confidence: 99%
“…C 11 -Pittsburg compound B-PET: PiB-PET) show that reduced neuronal glucose metabolism and increased levels of neocortical Aβ accumulation are features that occur early in the disease (see review ref. 15). A small number of cohort studies have investigated the relationship between these imaging markers of AD and T2D.…”
Section: Growing Evidence Supports the Hypothesis That Type 2 Diabetementioning
confidence: 99%